Qualitative analysis of facilitators and barriers to centre- and home-based exercise training in breast cancer patients - a Swiss tertiary centre experience (Swiss Medical Weekly, 2022)
BACKGROUND: Exercise is an effective therapy for breast cancer patients to reduce fatigue and to improve health-related quality of life and physical function. Yet breast cancer patients often do not meet the recommended physical activity guidelines. To better understand why recommendations are not met and to improve long-term physical activity maintenance, this study aimed at identifying facilitators and barriers of breast cancer survivors to supervised, centre-based exercise within a cardio-oncological rehabilitation programme and to unsupervised, home-based exercise both during and after the completion of the programme, as well as strategies used to manage these barriers.METHODS: Breast cancer patients who had previously completed a structured centre-based exercise programme at a Swiss tertiary centre were recruited by mailed invitation letter. Semi-structured telephone interviews were conducted with consenting patients and subsequent thematic analysis was performed to identify common themes.RESULTS: Of the 37 eligible breast cancer patients, 19 patients (51%, mean age 48.9 ± 9.7 years) responded to our invitation. Baseline characteristics did not differ from the total eligible population. General facilitators for exercise were anticipated and experienced benefits on physical and mental health and enjoyment of exercise. Facilitators specific for supervised centre-based exercise were social support, accountability and the provision of structured exercise by the programme. Centre-based exercise barriers included physical, psychological and environmental barriers, whereby psychological barriers were reported predominantly in the context of home-based exercise. Strategies to manage these barriers were diverse and included the adaptation of training circumstances, behaviour change strategies and strategies to deal with side effects.CONCLUSIONS: This first study on facilitators of and barriers to exercise in breast cancer patients in Switzerland identified more barriers, particularly psychological barriers, for unsupervised home-based exercise than for supervised centre-based exercise. These findings support the importance of providing structured supervised exercise programmes for breast cancer patients and suggest that a special focus should be directed at the transition from supervised to self-organized exercise in order to enhance and maintain long-term exercise participation.